2022
DOI: 10.1093/pnasnexus/pgac175
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic fields produced by subsea high-voltage direct current cables reduce swimming activity of haddock larvae (Melanogrammus aeglefinus)

Abstract: High Voltage Direct Current (HVDC) subsea cables are used to transport power between locations and from/to near-shore and off-shore facilities. HVDC cables produce magnetic fields (B-fields) that could impact marine fish. Atlantic haddock (Melanogrammus aeglefinus) is a demersal fish that is at risk of exposure to anthropogenic B-fields. Their larvae drift over the continental shelf, and use the Earth's magnetic field for orientation during dispersal. Therefore, anthropogenic MFs from HVDC cables could alter t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
4
1
Order By: Relevance
“…The observed MF-related decrease in swimming speed of lumpfish was smaller (this study: 16%) than that observed in Atlantic haddock larvae ( Melanogrammus aeglefinus ) (60%) exposed to slightly lower intensities ( Cresci et al, 2022a ; 150 µT, this study: ~200 µT). European eel ( Anguilla anguilla ) also reduced their swimming speed in the vicinity of a submarine power cable ( Westerberg & Lagenfelt, 2008 ).…”
Section: Discussioncontrasting
confidence: 73%
“…The observed MF-related decrease in swimming speed of lumpfish was smaller (this study: 16%) than that observed in Atlantic haddock larvae ( Melanogrammus aeglefinus ) (60%) exposed to slightly lower intensities ( Cresci et al, 2022a ; 150 µT, this study: ~200 µT). European eel ( Anguilla anguilla ) also reduced their swimming speed in the vicinity of a submarine power cable ( Westerberg & Lagenfelt, 2008 ).…”
Section: Discussioncontrasting
confidence: 73%
“…Electromagnetic fields (EMFs): submarine cables and electrical infrastructure associated with OWFs emit electromagnetic fields and potentially impact marine creatures [54]. Different fish species have shown different sensitivity to changes in EMF by either showing changes in behavior [55] or no reaction [56]. The information products required in this application are EMF levels and their potential effects on migratory patterns, behavior, and sensory systems of marine species.…”
Section: Ecological Impacts Of Owfsmentioning
confidence: 99%
“…Furthermore, the installation of wind turbines and the associated infrastructure (e.g., cables and substations) can cause physical habitat alteration and loss. For example, the installation of OWF can disrupt the seabed and benthic ecosystems and have an impact on the behavior of the marine species via the change in the electromagnetic fields, which is caused by undersea cables transmitting electricity from OWFs [111,112]. Furthermore, the currents around monopiles in OWFs increase turbulent mixing, potentially leading to the break-up of stratification [113,114], increased turbidity [115], and changes in primary production [6,116,117].…”
Section: Ecological Impacts Of Owfsmentioning
confidence: 99%